Ionic liquid‐based materials for electrochemical biosensing. Issue 3 (31st August 2022) - Khorsandi, Danial; Zarepour, Atefeh; Rezazadeh, Ilia; Ghomi, Matineh; Ghanbari, Roham; Zarrabi, Ali; Esfahani, Faranak Tarkesh; Mojahed, Nooshin; Baghayeri, Mehdi; Zare, Ehsan Nazarzadeh; Makvandi, Pooyan
Abstract: Due to their interesting features including negligible volatility, ease of designing in the construction, good chemical, and thermal stability, and excellent ionic conductivity, ionic liquids (ILs) have attracted a lot of attention to themselves in recent years. They are constructed from asymmetric anions and cations and are found in a liquid state lower than 100°C. Their unique features introduce them as candidates for the application in the structure of different types of electrochemical biosensors, in which they could act as electrolytes, or could be used as detecting agents. According to these features, this review aims to present an overview of the application of ILs in the structure of electrochemical sensors and biosensors. Based on this, after a brief description of the ILs and biosensors, the application of ILs in the structure of some of the recent electrochemical biosensors has been discussed and then, remarks and perspectives on these types of biosensors are explained. Abstract : Due to their interesting features including negligible volatility, ease of designing in the construction, good chemical, and thermal stabilities, and excellent ionic conductivity, ionic liquids (ILs) have attracted a lot of attention to themselves in recent years. They are constructed from asymmetric anions and cations and are found in a liquid state lower than 100°C. Their unique features introduce them as candidates for the application in the structure of different types of electrochemical biosensors, in which they could act as electrolytes, or could be used as detecting agents. According to these features, this review aims to present an overview of the application of ILs in the structure of electrochemical sensors and biosensors. Based on this, after a brief description of the ILs and biosensors, the application of ILs in the structure of some of the recent electrochemical biosensors has been discussed and then, remarks and perspectives on these types of biosensors are explained.